American Revenge Narratives A Collection of Critical Essays (Springer International Publishing, 2018)
American Revenge Narratives critically examines the nation's vengeful storytelling tradition. With essays on late twentieth and twenty-first century fiction, film, and television, it maps the coordinates of the revenge genre's contemporary reinvention across American culture. By surveying American revenge narratives, this book measures how contemporary payback plots appraise the nation's political, social, and economic inequities. The volume's essays collectively make the case that retribution is a defining theme of post-war American culture and an artistic vehicle for critique. In another sense, this book presents a scholarly coming to terms with the nation's love for vengeance. By investigating recent iterations of an ancient genre, contributors explore how the revenge narrative evolves and thrives within American literary and filmic imagination. Taken together, the book's diverse chapters attempt to understand American culture's seemingly inexhaustible production of vengeful tales.